Sorok piat' . Sorok piat' . Forty-five . Сорок пять - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Summary of the past year's academic results; a survey of the education press; discussion of problems in secondary school education. Featured in the program: Tkachenko, Evgenii Viktorovich (Education Minister of the Russian Federation) Contributors: Kucher, Irina (Anchor) Подведение итогов прошедшего учебного года; обзор педагогической прессы; обсуждение проблем школьного образования. В программе участвуют: Ткаченко, Евгений Викторович (Министр образования Российской Федерации) Создатели: Кучер, Ирина (Ведущий/Ведущая)